Isu Gender dan Kekerasan Seksual di Lembaga Pendidikan Islam - Suroso Suroso; Muhammad Hufron; Achwan Baharudin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
Gender equality is equality between men and women in accessing opportunities and rights as human beings, performing functions and participating in political, legal, economic, cultural and social activities. education, society and defense and security of this development. Gender equality also includes eliminating discrimination and structural injustice against men and women. The issue of gender equality is especially linked to the issue of unequal status between women and men. This cannot be separated from the patriarchal culture that still exists in society, whereby men dominate the family structure, where historically, women were considered incapable of managing the area. their own work and work without male leadership. The causes of sexual violence in educational institutions are mainly due to lack of government attention and management. Second, the way of thinking is not uniform. Third, there are unequal power relationships. Fourth, lack of education about sex and social ethics. The prevention of sexual violence must be implemented at all levels, including in Islamic educational institutions. Mechanisms to prevent sexual violence by following the principle of prevention are systematically structured and targeted.